2011
DOI: 10.1186/1750-1326-6-18
|View full text |Cite
|
Sign up to set email alerts
|

A new role for interferon gamma in neural stem/precursor cell dysregulation

Abstract: BackgroundThe identification of factors that compromise neurogenesis is aimed at improving stem cell-based approaches in the field of regenerative medicine. Interferon gamma (IFNγ) is a main pro-inflammatory cytokine and up-regulated during several neurological diseases. IFNγ is generally thought to beneficially enhance neurogenesis from fetal or adult neural stem/precursor cells (NSPCs).ResultsWe now provide direct evidence to the contrary that IFNγ induces a dysfunctional stage in a substantial portion of NS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
50
1
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(58 citation statements)
references
References 23 publications
5
50
1
2
Order By: Relevance
“…Previous studies have shown that murine NSCs express functional IFN-γ receptors [37]. We verified, using a quantitative RT-PCR, that IFN-γR1 was expressed in NSC from all passages of culture used in this study (Fig.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…Previous studies have shown that murine NSCs express functional IFN-γ receptors [37]. We verified, using a quantitative RT-PCR, that IFN-γR1 was expressed in NSC from all passages of culture used in this study (Fig.…”
Section: Resultssupporting
confidence: 80%
“…These effects are initiated by IFN-γ binding to its cognate receptor, which is widely expressed on NSCs and its derivative cells [37]. Data presented in the present study demonstrate that by blocking IFN-γ R1, either using a neutralizing antibody or IFN-γ R1 KO NSCs, effectively abrogates the inhibitory effects produced by activated CD8 lymphocytes, indicating that these effects are likely mediated through the IFN-γ receptor.…”
Section: Discussionmentioning
confidence: 50%
“…Inflated inflammatory factors increase the access of lymphocytes in the brain [10,17] to contribute inflammation, such as cytotoxic T-cell derived IFNγ contributes neuronal degeneration [26,50,87], and cause systemic effects after TBI [8,53,92]. In contrast, IFNγ contributes in M2 response [23], which is also associated with the prolonged blood infiltrated cells in the CNS [11,45,47,90].…”
Section: Discussionmentioning
confidence: 90%
“…Inflammation can affect various phases of adult neurogenesis. For example, pro-inflammatory cytokine interleukin 6 (IL-6), results in decreased proliferation (Vallieres et al, 2002); whereas other pro-inflammatory cytokines such as interferon-gamma (IFN-γ) can alter fate choices from neuronal to astrocytic (Walter et al, 2011). …”
Section: Potential Mechanisms Of Alcohol's Effects On Adult Neurogmentioning
confidence: 99%